Effect of Zeolite and Seaweed Extract on Soil Properties and Morphological Traits of Rosa Damascena for Environmentally Sustainable Production - Shahad, Raad Frahan; Hamid, Mustafa Qais; Hundi, Huda Krebit (Research in Ecology, 2025)
This study investigates the effects of natural zeolite and seaweed extract (SWE) on soil properties and morphological traits of Rosa damascena grown in Zemij soil under greenhouse conditions. Zeolite was applied at concentrations of 0, 5, and 10 mg L−1, while SWE was foliar-applied at 0, 10, and 30 mL L−1 using a randomized complete block design. The results showed that SWE significantly improved plant height, number of leaves, lateral shoots, leaf area, and both shoot and root dry weights, with the most notable effects at 30 mL L⁻¹. Although zeolite had a limited individual impact, its interaction with SWE-particularly at 5 mg L−1-led to synergistic improvements in root growth. From an environmental perspective, the findings suggest that both zeolite and SWE can serve as sustainable biostimulants, reducing dependence on chemical fertilizers. This approach contributes to improving soil fertility and resilience against degradation, while minimizing environmental pollution commonly associated with conventional agricultural inputs. The use of these natural amendments in low-fertility soils offers an environmentally friendly and economically viable option for sustainable ornamental plant production, particularly for high-value species like Rosa damascena. These findings support using zeolite and seaweed extract as natural biostimulants to improve plant growth and soil quality, particularly in low-fertility soils. Further research should explore their effects on other crops and assess long-term impacts on soil fertility, water efficiency, and environmental sustainability, offering a viable alternative to chemical fertilizers.